2017
DOI: 10.1161/circulationaha.117.030137
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Stimulus Determines Lineage Commitment of Cardiac C-kit + Cells

Abstract: Background Although cardiac c-kit+ cells are being tested in clinical trials, the circumstances that determine lineage differentiation of c-kit+ cells in vivo are unknown. Recent findings suggest endogenous cardiac c-kit+ cells rarely contribute cardiomyocytes to the adult heart. We assessed whether various pathological stimuli differentially affect the eventual cell fates of c-kit+ cells. Methods We employed single cell sequencing and genetic lineage tracing of c-kit+ cells to determine whether various path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Indeed, genetic lineage-tracing models have shown that c-Kit is expressed in a subpopulation of endothelial cells 12 that double after MI 11 and that cardiomyocytes rarely express c-Kit or originate from c-Kit + cells 11 , 13 , 14 . One lineage-tracing study reported a modest increase in c-Kit-expressing cardiomyocytes following TAC-induced PO, although the increase was below clinically-relevant levels 45 . However, genetic lineage-tracing Kit-Cre models that result in haploinsufficiency of the c-Kit gene have been questioned, as reviewed 46 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genetic lineage-tracing models have shown that c-Kit is expressed in a subpopulation of endothelial cells 12 that double after MI 11 and that cardiomyocytes rarely express c-Kit or originate from c-Kit + cells 11 , 13 , 14 . One lineage-tracing study reported a modest increase in c-Kit-expressing cardiomyocytes following TAC-induced PO, although the increase was below clinically-relevant levels 45 . However, genetic lineage-tracing Kit-Cre models that result in haploinsufficiency of the c-Kit gene have been questioned, as reviewed 46 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposing aged animals or cells to young microenvironment has been shown to reverse ageing phenotypes [35,36,37,38,39], but Wharton’s Jelly MSCs did not rejuvenate aCCs in co-culture. This may be attributed to insufficient MSC coculture time to observe an effect in aCCs which were chronically exposed to surrounding ageing stimuli in vivo [40], i.e., the senescence associated secretory phenotype (SASP) [41], a known cell senescent accelerator [42]. Nonetheless, our data shows that MSCs improved aCC migration and proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, it is possible that there is a labile cardiomyogenic stem cell population, which is progressively eliminated by DOX treatment over time. However, recent results using a lineage trace system demonstrated that DOX treatment actually enhances cardiomyogenic activity in putative c-kit progenitor cells, 30 thus a permanent reduction in transgene-induced cardiomyocyte S-phase activity would not be anticipated (particularly since the MHC-cycD2 transgene would not be expected to be expressed in a progenitor cell which has not yet adopted a cardiac phenotype).…”
Section: Discussionmentioning
confidence: 99%